Rastreio da fragilidade, sarcopenia, dinapenia e força muscular respiratória em idosos hospitalizados - Camargo, Ana Luiza de Arruda (2024)
Introduction: The increase in life expectancy in recent years has led to a scenario of greater predisposition to multimorbidities and the presence of geriatric syndromes, such as frailty, sarcopenia and dynapenia, making the elderly vulnerable to decompensation and hospitalization. The reduction of mobility and functional capacity is the target of mainly outpatient studies, and in the hospital, in view of the immobility imposed, more and more strategies have been sought to minimize the impacts of hospitalization in the elderly. Objectives: To screen frailty, sarcopenia, dynapenia, nutritional aspects, and muscle and respiratory strength in hospitalized older adults. Methods: This is a prospective, observational study in which patients over 60 years of age hospitalized for clinical treatment were evaluated. The patients underwent evaluations to screen for frailty, sarcopenia, dynapenia, nutritional evaluation, and measurement of handgrip and respiratory strength. Results: All elderly patients had some degree of frailty and slightly more than half had suspected sarcopenia, as well as dynapenia. Pre-frail older adults showed higher MIP when compared to frail older adults, and in addition, half of the older adults who underwent the respiratory muscle strength test showed weakness. The comparison between the presence and absence of dynapenia and variables such as age, gender, length of hospital stay, deaths, IPAQ, unintentional weight loss, and rMAN, was significant only when compared with age. HGS is higher in older adults with better IMMEA, nutritional status, and lower Sarc-F scores. Conclusion: Most hospitalized elderly patients present frailty, dynapenia, suspected sarcopenia, malnutrition, or nutritional risk. Handgrip strength was an important and easy variable to assess, and was related to skeletal muscle mass, nutritional status, and suspected sarcopenia. The reduction in respiratory muscle strength is significantly related to frailty.